DNA Damage and Oxidative Stress in Patients with Osteoarthritis: a Pilot Study - Özlem Altındağ; Abdurrahim Koçyiğit; Necla Çelik; Hakim Çelik; Neslihan Soran (Archives of Rheumatology, 2007)
Objective: We aimed to investigate the effect of osteoarthritis on basal levels of DNA strand breaks and on the oxidative/anti-oxidative status of patients with osteoarthritis, and healthy subjects. Patients and Methods: The study population contained 29 patients with knee osteoarthritis and 26 healthy controls. We used single-cell gel electrophoresis (also called comet assay) to measure DNA strand breaks in peripheral blood mononuclear leukocytes. Plasma levels of total antioxidant status (TAS) and total oxidative status (TOS) were determined, and oxidative stress index OSI was calculated using a novel automated measurement method. Results: The mean values of DNA damage, plasma TOS and OSI were significantly higher in patients with osteoarthritis than in controls (p < 0.001, for all). Plasma TAS level was lower in patients than in healthy controls (p < 0.001). There was a significantly positive correlation between OSI and DNA damage (r = 0.530, p < 0.001). Conclusion: The findings indicated that Reactive Oxygen Species produced in the progression of the disease may induce oxidative damage in normal cells. (Rheumatism 2007; 60-3)